Dietary intakes and daily distribution patterns of macronutrients in youth soccer players - Martinho, Diogo V.; Naughton, Robert J.; Leão, César; Lemos, João; Field, Adam; Faria, Ana; Rebelo, André; Gouveia, Élvio R.; Sarmento, Hugo (Frontiers in Nutrition, 2023)
There has been an abundant of dietary analysis research conducted in male adult soccer players while, studies within youth players are lacking. Furthermore, the daily distribution of energy and macronutrient intake across the day have been reported to impact on training adaptations, but this is often not considered in the literature. The aims of this study were: to quantify daily energy and macronutrient intake and assess their distribution across five days; and to compare daily energy intake and predicted daily energy expenditure in under-16 male soccer players. The sample included 25 soccer participants aged 14.8-15.7 years-old. Five-day self-reported food diaries were used to collect the food/drink consumed. Intake was analysed for total daily energy and macronutrient intake, as well as the distribution between meals (breakfast, lunch, dinner and snacks). Daily energy expenditure was predicted by resting energy expenditure and physical activity level developed for youth sport participants. The total mean energy intake was 1928±388 kcal∙day-1 whereas the estimated daily energy expenditure was 3568 kcal∙day-1. The relative daily protein intake was lower at breakfast, morning snack, afternoon snack and night snack compared to lunch and dinner. Youth soccer players appear to not meet energy demands and daily CHO guidelines. Fluctuations across the day on protein intake were noted and may influence training adaptations (i.e. muscle protein synthesis and recovery).